Identification and characterization of endogenous retroviruses upon SARS-CoV-2 infection - Guo, Xuefei; Zhao, Yang; You, Fuping (Frontiers in Immunology, 2024)
Endogenous retroviruses (ERVs) derived from the long terminal repeat (LTR) family of transposons constitute a significant portion of the mammalian genome, with origins tracing back to ancient viral infections. Despite comprising approximately 8% of the human genome, the specific role of ERVs in the pathogenesis of COVID-19 remains unclear. In this study, we conducted a genome-wide identification of ERVs in human peripheral blood mononuclear cells (hPBMCs) and primary lung epithelial cells from monkeys and mice, both infected and uninfected with SARS-CoV-2. We identified 405, 283, and 206 significantly up-regulated transposable elements (TEs) in hPBMCs, monkeys, and mice, respectively. This included 254, 119, 68, and 28 ERVs found in hPBMCs from severe and mild COVID-19 patients, monkeys, and transgenic mice expressing the human ACE2 receptor (hACE2) and infected with SARS-CoV-2. Furthermore, analysis using the Genomic Regions Enrichment of Annotations Tool (GREAT) revealed certain parental genomic sequences of these up-regulated ERVs in COVID-19 patients may be involved in various biological processes, including histone modification and viral replication. Of particular interest, we identified 210 ERVs specifically up-regulated in the severe COVID-19 group. The genes associated with these differentially expressed ERVs were enriched in processes such as immune response activation and histone modification. HERV1_I-int: ERV1:LTR and LTR7Y: ERV1:LTR were highlighted as potential biomarkers for evaluating the severity of COVID-19. Additionally, validation of our findings using RT-qPCR in Bone Marrow-Derived Macrophages (BMDMs) from mice infected by HSV-1 and VSV provided further support to our results. This study offers insights into the expression patterns and potential roles of ERVs following viral infection, providing a valuable resource for future studies on ERVs and their interaction with SARS-CoV-2.